Морфологические изменения в строении генеративных органов некоторых видов семейства Rosaceae Juss. в Донбассе - Лиханов, А.Ф. (Промышленная ботаника, 2002)
In the spring of 2001 the mass appearance of flowers with indications of teratologic changes were observed in plants of Rosaceae family on the background of technogenic pollution and adverse weather conditions in Donetsk. Various anomalies in flowers structure of 17 plant species have been revealed and described. Some aspects of teratogenesis dynamics in Fragaria vesca L. generative organs have been investigated. Quantitative estimation of heavy metals contents in plant material has been carried out. There have been detected, that the anomalies of apricot, cherry and apple flowers result in significant decrease of seed production of plants.